Improving Community Preparedness Through Disaster Management Training in Sukaraja Village, Medan Maimun District, Medan City - Ismayadi; Harahap, Ikhsanuddin Ahmad (Talenta Publisher, 2024)
Disaster mitigation is generally implemented to reduce losses caused by potential disasters, including both loss of life and property damage, which can significantly impact human activities and livelihoods. In Sukaraja Village, the community’s understanding of disaster response is limited to basic actions such as evacuating to higher and safer ground during floods. However, the community often faces challenges in evacuating vulnerable groups, such as women, the elderly, and children, due to the densely populated area and limited evacuation space. This service program aimed to address these challenges by conducting a comprehensive training on disaster mitigation, focusing on evacuation and first aid for flood victims by the members of the Disaster-Resilient Village Forum (Keltana). The method employed in this community service program included structured training sessions and simulations, comprising: (1) educational sessions on knowledge, attitudes, and actions required during flood emergencies, (2) hands-on training on evacuation procedures and first aid techniques for disaster mitigation, and (3) Communication, Information, and Education (CIE) activities on emergency response strategies targeted at Keltana members. The results showed a significant improvement in the participants’ understanding and skills. The training increased the knowledge level of Keltana members on flood evacuation and first aid from 55% to 93%. Additionally, the program enhanced their practical skills in evacuating flood victims and administering first aid for injuries, including fractures and bleeding. In conclusion, the disaster mitigation training program successfully strengthened the community’s capacity in flood response, contributing to improved resilience and preparedness in Sukaraja Village. The approach and outcomes of this program can serve as a model for similar high-risk areas to enhance community-based disaster mitigation efforts.